Silver linings on the horizon: highlights from the 10th Cachexia Conference. Issue 1 (8th February 2018) - Ebner, Nicole; von Haehling, Stephan
Abstract: This article highlights the updates from preclinical and clinical studies into the field of wasting disorders that were presented at the 10th Cachexia Conference held in Rome, Italy, in December 2017. This year's conference saw some interesting results of larger‐scale studies and clinical trials and new therapeutic targets. Herein, we summarize the biological and clinical significance of different markers and new diagnostic tools and cut‐offs for the detection of skeletal muscle wasting, including micro RNAs, the ubiquitin‐proteasome system, mTOR signalling, news in body composition analysis including the D3‐creatine dilution method, and new biomarkers. Clinical studies investigated novel nutritional approaches, trials of elamipretide, enobosarm, and urolithin A. It remains a fact, however, that effective treatments of cachexia and wasting disorders are urgently needed in order to improve patients' quality of life and their survival.